Legal And Regulatory Challenges Of Halal Certification: Insights From Cosmetic Manufacturers On Halal Built-in Implementation - Yuhanza Othman; Hendun Abd Rahman Shah; Muhammad Nizam Awang (Human Resource Management Academic Research Society, 2024)
Indexed by Era